Análise da transição epitélio-mesênquima e de receptores de fator de crescimento epidérmico em melanomas cutâneos e de cavidade oral em cães - Emerson Soares Veloso (2018)
Melanoma is characterized by abnormal proliferation of melanocytes and constitutes the most aggressive cutaneous neoplasm in both dogs and humans. During a neoplastic progression of melanomas, there is loss of interaction of the microenvironment keratinocytes besides disordered proliferation, characteristics that together lead to invasion of the underlying tissues. The reduced interaction observed between neoplastic melanocytes and keratinocytes is due to loss of E-cadherin expression and N-cadherin gain, which facilitates adhesion to fibroblasts and endothelial cells, forming the epithelial-mesenchymal transition (EMT). The disordered proliferation is associated, among other factors, with the overexpression of epidermal growth factor receptors, especially EGFR. These events are well described in human melanomas and experimental murine melanomas, but few studies on canine melanomas address this issue. Thus, in this work we aimed to identify the expression and relation between molecules related to epithelial-mesenchymal transition and epidermal growth factors receptors with the progression of canine, oral and cutaneous, melanoma. In the studied cases, approximately half of them did not present E-cadherin expression whereas almost all had N-cadherin expression, which was interestingly observed also in the cytoplasm and nucleus of the neoplastic cells. The nonmembrane expression of N-cadherin was associated with the presence of the transcription factor ZEB1, whereas the membrane N-cadherin was associated with the expression of ZEB2, since the association between the Snail transcription factor and N-cadherin appears to be altered by the oral or cutaneous location of the lesion differently from that observed for the other factors studied. The proliferative index of cutaneous lesions was associated with increased Her-4 cytoplasmic expression and reduction of EGFR and Her-3. In the oral lesions Her-2 membrane expression was associated with the presence of emboli, however, no ERBB2 gene amplification was observed. Thus, our work evidences the occurrence of EMT in canine melanomas and also the translocation of the N-cadherin membrane protein to cytoplasm and nucleus, which is apparently regulated by the ZEB transcription factors and the apparent participation of Her-4 in stimulating proliferation and of EGFR and Her-3 in stimulating cell differentiation, in addition to the relationship between Her-2 and the presence of neoplastic emboli.